2021
DOI: 10.1002/ehf2.13219
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor blockade with finerenone improves heart function and exercise capacity in ovariectomized mice

Abstract: Aims In post-menopausal women, incidence of heart failure with preserved ejection fraction is higher than in men. Hormonal replacement therapies did not demonstrate benefits. We tested whether the non-steroidal mineralocorticoid receptor antagonist finerenone limits the progression of heart failure in ovariectomized (OVX) mice with metabolic disorders. Methods and results Ovariectomy was performed in 4-month-old mice, treated or not at 7 months old for 1 month with finerenone (Fine) 1 mg/kg/day. Left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Treatment with spironolactone also prevented diet-induced diastolic dysfunction and arterial stiffness in female mice (De Marco et al, 2015). Finerenone improved HFpEF by decreasing LV filling pressure, increasing LV compliance, and prevented coronary endothelial dysfunction in ovariectomized mice (Pieronne-Deperrois et al, 2021).…”
Section: Hypertensive Modelsmentioning
confidence: 89%
“…Treatment with spironolactone also prevented diet-induced diastolic dysfunction and arterial stiffness in female mice (De Marco et al, 2015). Finerenone improved HFpEF by decreasing LV filling pressure, increasing LV compliance, and prevented coronary endothelial dysfunction in ovariectomized mice (Pieronne-Deperrois et al, 2021).…”
Section: Hypertensive Modelsmentioning
confidence: 89%
“…In transgenic mice with cardiac‐specific overexpression of Rac1 and increased left ventricular volumes, finerenone blocked left ventricular fibrosis and dilation (Lavall et al, 2019). Finally, finerenone improved heart failure with preserved ejection fraction by decreasing LV filling pressure, increasing LV compliance and prevented coronary endothelial dysfunction in ovariectomized mice (Pieronne‐Deperrois et al, 2021).…”
Section: Animal Modelsmentioning
confidence: 99%
“…In ovariectomized mice with left ventricular diastolic dysfunction and preserved ejection fraction, finerenone improved left ventricular filling, coronary artery endothelium-dependent relaxation, mitochondrial ATP production, and exercise capacity [ 41 ]. Experimental studies of finerenone have also shown improvement in metabolic parameters, such as the average size of adipocytes, adipocyte differentiation, fat deposits, type of fat, and oxidative stress [ 42 , 43 ].…”
Section: Finerenone Slows the Progression Of Ckd And Reduces The Risk...mentioning
confidence: 99%